Knowledge Level of Silkworm Rearers of Jammu Division of Jammu and Kashmir State - Lyaqet Ali , S. K .Kher , P. S. Slathia , R.K.Bali , Manish Kumar and P. Bakshi, (Indian Journal of Extension Education, 2016)
The present study was carried out to know the knowledge level of silkworm rearers of Jammu division. The study revealedthat from three districts 60.00 per cent of respondents had medium knowledge followed by 32.92 per cent respondents hadlow knowledge and 15.36 per cent respondents had high knowledge respectively. The overall mean knowledge score was15.36 (+ 2.29). Majority of respondents (93.33%) had knowledge of time of pruning, (82.91%) of respondents hadknowledge of insects of mulberry plants,(90.41%) and (83.75%) had knowledge of methods of disinfecting the silkwormbody and rearing seat and disinfectants used for rearing room and appliances, (95.41%), (82.91%) and (78.75%) hadknowledge of control of insect/pest of silkworm, management of diseases, insect pest of silkworm and important diseasesof silkworms, (88.75%) and (83.26%) had knowledge of late age silkworm rearing techniques and low cost devices forcocoon stifling, low percentage of respondents had knowledge of length and thickness of mulberry cuttings forpropagation and only (27.08%) respondents had knowledge of improved variety of mulberry, Less percentage ofrespondents had knowledge of method of silkworm incubation, temperature cum humidity requirement for young as wellas late age rearing.